Optimization of Raw Materials Stock Eggtray PT. Era Light Box Gresik Using Genetic Algorithm - Dwiki Ashari Kusumawardhana; Wiwiet Herulambang (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
Obstacles that occur today in the PT. Era ray Box still use manual calculation for the stock of rawmaterials, so the impact on the delay in the department information and management company itself. In additionthe company also often lose money because the number of ordering goods is increasing and are still usingmanual calculation so that the risk of causing an invalid calculation and not achieving the target onproduction.Genetic algorithms are search techniques in computer science to find a settlement forecasts foroptimization and search problems. The results of the optimization experiments that have been carried out, theresults obtained are different by comparing the 10 iterations, 100 iterations and 1000 iterations. From theexperiments performed by the user with a genetic algorithm system in the output of raw materials Dregs S.awal2438333333 kg, Dregs Exit 3002885622 kg, 342 kg S.awal spindles, spindles Exit 1069444444 kg, 988 kgS.awal Carton, Cardboard Exit 9358 kg, obtained the best fitness value is 28679.2.